Ni pasividad ni resistencia. Modos competitivos de construcción de ciudadanía desde la dirigencia barrial - Luján, David (Pontificia Universidad Católica del Perú. Fondo Editorial, 2019)
This essay tries to answer the following questions: how and under what conditions do social actors become citizens? And how does the principle of citizenship work among different groups? Through a qualitative and ethnographic methodology focused on the stories of sixty neighborhood leaders in a Chilean commune, we propose 1) citizenship as a series of links between society and the State, in which meanings are daily constructed around social inclusion and exclusion, which are brought into play in face-to-face contacts through differentially distributed resources, skills and capacities; 2) sociopolitical ties beyond the absolute distinction between clientelist and contestatory actors to analyze their similarities and differences.

En este ensayo, se propone responder las preguntas: .como y en que condiciones los actores sociales se convierten en ciudadanos? y .como funciona el principio de ciudadania entre distintos colectivos?.A traves de una metodologia cualitativa y etnografica centrada en los relatos de sesenta dirigentes vecinales en una comuna de Chile, se propone una lectura de 1) la ciudadania como una serie de vinculos entre la sociedad y el Estado en que se intitulan cotidianamente sentidos en torno a la inclusion y exclusion social, los cuales son puestos en juego en contactos cara a cara a traves de recursos, habilidades y capacidades diferencialmente distribuidos; y 2) los vinculos sociopoliticos mas alla de la distincion absoluta entre actores clientelares y contestatarios para analizar sus similitudes y diferencias.
Neither passivity nor resistance: Competitive ways of building citizenship from the neighborhood leadership
Keywords: Clientelismo; Protesta; Ciudadanía; Vida cotidiana; Etnografía; https://purl.org/pe-repo/ocde/ford#5.04.00